Quantum Decision Theory and the Ellsberg Paradox - Ali al-Nowaihi; Sanjit Dhami; Mengxing Wei (Center for Economic Studies and ifo Institute (CESifo), 2018)
We formulate a simple quantum decision model of the Ellsberg paradox. We report the results of an experiment we performed to test the matching probabilities predicted by this model using an incentive compatible method. We find that the theoretical predictions of the model are in conformity with our experimental results. We compare the predictions of our quantum model with those of probably the most successful non-quantum model of ambiguity, namely, the source dependent model. The predictions of our quantum model are not statistically significantly different from those of the source dependent model. The source dependent model requires the specification of probability weighting functions in order to fit the evidence. On the other hand, our quantum model makes no recourse to probability weighting functions. This suggests that much of what is normally attributed to probability weighting may actually be due to quantum probability.
Keywords: D03; 330; quantum probability; the Ellsberg paradox; the source dependent model; the law of total probability; the law of reciprocity; the Feynman rules; projective expected utility; bounded rationality; Diebold-Mariano forecasting tests